Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Debark University - International Livestock Research Institute; Debark University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Debark University. On March 15, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Jajaw Demamu, President of Debark University.